Learning Space and Space for Learning: Adults’ Intersubjective Experiences of Improvisation - Pamela Meyer (Adult Education Research Conference, 2006)
This phenomenological study asked the question, “What do adults experience learning improvisation?” The findings highlight the intersubjective, whole-person nature of learning and transformation, and of the learning space.
Keywords: Transformative learning; improvisation; learning space; intersubjectivity; whole-person learning; phenomenology